Clinic-morphological characteristics of Cryptococcosis in HIV-infective patients - I. P. Charushina; N. V. Zotova (Журнал инфектологии, 2014)
The present article contains the results of observation for 8 generalized cryptococcosis patients with HIVinfection. The disease occurred in the presence of strongly marked immunodeficiency (the reduction of CD-4 lymphocytes less than 100 cells/mkl) in generalized form with the damage of central nervous system and without any clinical features of internal disturbances. The disease was characterized by severe progressing course of the infection which led to lethal outcome in 5 cases. Pathomorphological appearance was presented by multiple necrotic focuses with cryptococcus accumulation in brain, lungs, liver, lien, lymphatic nodes, intestines. Early complex diagnosis including obligatory mycological examination of liquor and other pathological material and timely added adequate antimycotic therapy are obligatory conditions for effective treatment of cryptococcosis. The clinical example of effective treatment of invasive cryptococcosispresented.